Effects of mixed antimicrobial peptide on the growth performance, antioxidant and immune responses and disease resistance of Pengze crucian carp (Carassius auratus var. Pengze). Issue 114 (July 2021) - Wang, Shaodan; Xie, Shaolin; Zhou, Aiguo; Zhang, Chaonan; Wen, Liufa; Xu, Guohuan; Zou, Jixing
Abstract: Antimicrobial peptides have broad-spectrum antibacterial properties and low drug resistance, and they demonstrate great potential as antibiotic substitutes. In this study, five dietary mixed antimicrobial peptide supplement groups were set and fed to Pengze crucian carp for 10 weeks. The 6 groups were G0 (control group) and 5 additional groups: G1 (100 mg/kg), G2 (200 mg/kg), G3 (400 mg/kg), G4 (800 mg/kg) and G5 (1600 mg/kg). The results showed that the final body weight (FBW), weight gain rate (WGR) and specific growth rate (SGR) of fish in G1 and G2 were higher than those of fish in the control group, and G1 was significantly higher than G0 (P < 0.05). In addition, the FBW, WGR, and SGR of the G3 group were significantly lower than those of the G0 group. The chymotrypsin, lipase and amylase activities of G1 and G2 were significantly upregulated compared with G0 and reached peak values in G1. The activity of T-AOC and SOD in the addition group was higher (except G2 and G4) than that in the control groups, and significantly increased in G3 compared to the control group. The activity of MDA in the addition group was lower than that in the control group (p > 0.05). The expression levels of TLR-4, MYD88 and TNF-α in the three organs of the addition group were higher than those in G0 and reached the peak value in G3 (p < 0.05). Furthermore, the expression levels of TLR-4, MYD88 and TNF-α in the three organs of G3 were significantly lower than those in G0 and lower than those in the other supplemented groups. The expression levels of IL-10 and IL-11 tended to be upregulated after A. hydrophila challenge, and G3 in different organs was significantly higher than that in other supplemented groups and G0. The results of this study show that an appropriate amount of mixed antimicrobial peptides can improve the growth performance and antioxidant and immune capabilities of Pengze crucian carp and can also play a positive role in the treatment of A. hydrophila infection. Highlights: Antimicrobial peptides affect fish growth, antioxidant and immune capacity. Low-dose antimicrobial peptides can significantly promote growth. High-dose antimicrobial peptides can significantly enhance immunity and inhibit growth to a certain extent. Antimicrobial peptides have a significant effect on the resistance of Aeromonas hydrophila.